Pendekatan Fiskal Keruangan untuk Pengembangan Wilayah Pulau-Pulau Kecil Perbatasan yang Berkelanjutan di Kabupaten Kepulauan Anambas - Ma'rif, Samsul; Hadi, Sudharto P; Maryono, Maryono (Department of Urban and Regional Planning, Diponegoro University, 2023)
The problem of small border islands in the Anambas Islands Regency in the Riau Islands Province related to development policy interventions is still lacking. Remote geographical location, economic scale of business, inadequate transportation conditions, limited facilities and infrastructure such as electricity, roads, telecommunications, clean water, etc. another small island in the vicinity. In connection with these problems, descriptively, this paper tries to initiate the need for increased development interventions through the application of economic fiscal policy combined with the allocation of space utilization according to the ecological carrying capacity of the environment. Through an economic-ecological approach in the form of implementing spatial fiscal allocations, the government's role as a development actor becomes the main driver for the sustainable development of small border islands. Government intervention through a spatial fiscal approach in the form of spending on goods and services, employee salaries and transfer payments will be the initial mover of the multiplier effect process of development activities. Furthermore, it will gradually attract the private sector or the business world to be involved in investing in the development of small border islands in a sustainable manner.